MicroRNAs hsa-miR-618 and hsa-miR-297 Might Modulate the Pleiotropic Effects Exerted by Statins in Endothelial Cells Through the Inhibition of ROCK2 Kinase: in-silico Approach - Leal, Karla; Saavedra, Kathleen; Rebolledo, Camilo; Salazar, Luis A. (Frontiers in Cardiovascular Medicine, 2021)
Several studies show that statin therapy improves endothelial function by cholesterol-independent mechanisms called "pleiotropic effects". These are due to the inhibition of the RhoA/ROCKs kinases pathway, its inhibition being an attractive atheroprotective treatment. In addition, recent work has shown that microRNAs, post-transcriptional regulators of gene expression, can affecting the response of statins and their efficacy. For this reason, the objective of this study was to identify by bioinformatic analysis possible new microRNAs that could modulate the pleiotropic effects exerted by statins through the inhibition of ROCK kinases. A bioinformatic study was performed in which the differential expression of miRNAs in endothelial cells was compared under two conditions: Control and treated with simvastatin at 10 μM for 24 hours, using a microarray. Seven miRNAs were differentially expressed, three up and four down. Within the up group, the miRNAs hsa-mir-618 and hsa-mir-297 present as a predicted target to ROCK2 kinase. Also, functional, and enriched pathway analysis showed an association with mechanisms associated to atheroprotective effects. This work shows an in-silico approach of how post-transcriptional regulation mediated by miRNAs could modulate the pleiotropic effects exerted by statins on endothelial cells, through the inhibition of ROCK2 kinase and its effects.